Доставка ліпофільних спінових зондів вуглецевими нанотрубками в еритроцити та плазму крові - Ivanov, L. V.; Lyapunov, O. M.; Kartel, M. T.; Nardid, O. A.; Оkotrub, A. V.; Kirilyuk, I A.; Cherkashina, Ya. O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
Using the method of electron spin resonance assessed binding (non-covalent adsorption) of several spin probes, which are paramagnetic model lipophilic physiologically active substances, carbon nanotubes with different structures, and features of the transition (transdiffusion) probes with nanotubes on the surface proteins of plasma and erythrocyte membrane in contact (incubation) with blood components. It is shown that the lipophilic probes having no ionic groups form stable complexes with mono- and multi-walled carbon nanotubes, whereas the probe with a quaternary ammonium group on the tubes practically do not adsorbed. Upon contact complexes "nanotube-probe" with the plasma and red blood cells in experimental animals within a few hours there is desorption probes (up to 15%) due to their interaction with plasma proteins as well as progressive penetration into lipid double layer erythrocyte membrane. It is demonstrated that the method of spin probes allows assessing the effectiveness of nanotubes as delivery means of targeted substances to target cells and to determine the localization of the probe in the membranes and intracellular space.